Pengaruh Terpaan Line Webtoon Killstagram Terhadap Kecemasan Menggunakan Hashtag di Instagram Pada Remaja Kota Denpasar - Peratiwi, Ni Made Candra Ari; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2022)
One of the famous Line Webtoon titles in the horror genre is Line Webtoon Killstgaram "Series Murder Through Hashtag". Line Webtoon Killstagram "Series Murder Through Hashtag" tells about the terror of murder because of the use of hashtags on his Instagram social media.Anxiety is defined as a feeling of restlessness, worry and fear. The purpose of this study was to explain how the influence of KIllstagram's Line Webtoon exposure to anxiety using hashtags on Instagram in teenagers in Denpasar City. This research uses explanative quantitative research method with uses and effects theory. This study also involved 210 teenagers in Denpasar City, aged 14 – 24 years. The results of this study indicate that Line Webtoon Killstagram exposure has a positive and significant effect on anxiety using hashtags on Instagram in Denpasar City teenagers. When Line Webtoon Killstagram's exposure increases, the anxiety of using hashtags on Instagram will also increase. Keywords: Line Webtoon, Line Webtoon Killstagram, Anxiety, Instagram